Formation of Interstellar Silicate Dust via Nanocluster Aggregation: Insights From Quantum Chemistry Simulations - Rimola, Albert; Bromley, Stefan T. (Frontiers in Astronomy and Space Sciences, 2021)
The issue of formation of dust grains in the interstellar medium is still a matter of debate. One of the most developed proposals suggests that atomic and heteromolecular seeds bind together to initiate a nucleation process leading to the formation of nanostructures resembling very small grain components. In the case of silicates, nucleated systems can result in molecular nanoclusters with diameters  2 nm. A reasonable path to further increase the size of these proto-silicate nanoclusters is by mutual aggregation. The present work deals with modelling this proto-silicate nanocluster aggregation process means of quantum chemical density functional theory calculations. We simulate nanocluster aggregation by progressively reducing the size of a periodic array of initially well-separated nanoclusters. The resulting aggregation leads to a set of silicate bulk structures with gradually increasing density which we analyse with respect to structure, energetics and spectroscopic properties. Our results indicate that aggregation is a highly energetically favourable process, in which the infrared spectra of the finally formed amorphous silicates match well with astronomically observations.